The Influence Of LDR, ROE, NIM, And BOPO On Changes In Banking Company Profits (Empirical Study On Banking Sector Companies Listed On The Indonesia Stock Exchange (IDX) 2018-2022) - Jordan Adam Setiawan; Gideon Setyo Budiwitjaksono (Jurnal Ekonomi, 2024)
The objective of this study is to ascertain and evaluate the impact of the Loan to Deposit Ratio (LDR), Return on Equity (ROE), Net Interest Margin (NIM) and Operating Expenses on Operating Income (BOPO) on changes in profits of banking sector companies listed on the Indonesia Stock Exchange (IDX) over the period 2018-2022. This research employs a quantitative approach utilizing secondary data from annual financial reports and audited financial reports of conventional banks sourced from the official website of the Indonesia Stock Exchange (www.idx.co.id). A purposive sampling technique was utilized to select a sample of 135 observations over a five-year research period. The data analysis employed a multiple linear regression analysis technique. The findings of this study indicate that the combined influence of liquidity ratio (LDR), return on equity (ROE), net interest margin (NIM), and cost-to-income ratio (BOPO) has a statistically significant effect on changes in profit. However, while liquidity ratio and return on equity have a significant effect on profit changes, net interest margin and cost-to-income ratio do not.